2023
DOI: 10.1098/rsbl.2023.0307
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomics of weevils revisited: data curation and modelling compositional heterogeneity

Yan-Da Li,
Michael S. Engel,
Erik Tihelka
et al.

Abstract: Weevils represent one of the most prolific radiations of beetles and the most diverse group of herbivores on land. The phylogeny of weevils (Curculionoidea) has received extensive attention, and a largely satisfactory framework for their interfamilial relationships has been established. However, a recent phylogenomic study of Curculionoidea based on anchored hybrid enrichment (AHE) data yielded an abnormal placement for the family Belidae (strongly supported as sister to Nemonychidae + Anthribidae). Here we re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 71 publications
(121 reference statements)
0
1
0
Order By: Relevance
“…PPAs indicated that CAT-GTR + G4 ( Z -score = 3.974), the model that was favoured based on my model comparison test, describes site-specific amino acid preferences substantially better than other tested models. This result was not surprising, since CAT-GTR + G4 is known to be by far the best-fitting model that can explicitly accommodate among-site compositional heterogeneity 21 24 .…”
Section: Resultsmentioning
confidence: 88%
“…PPAs indicated that CAT-GTR + G4 ( Z -score = 3.974), the model that was favoured based on my model comparison test, describes site-specific amino acid preferences substantially better than other tested models. This result was not surprising, since CAT-GTR + G4 is known to be by far the best-fitting model that can explicitly accommodate among-site compositional heterogeneity 21 24 .…”
Section: Resultsmentioning
confidence: 88%
“…'s ( 2019 ) data with the site‐heterogeneous model CAT‐GTR + G4. Site‐heterogeneous models could generally improve the accuracy of phylogenetic analyses (e.g., Li, Engel, et al., 2023 ), and specifically, compared with Gimmel et al. ( 2019 ), the result by Li et al.…”
Section: Methodsmentioning
confidence: 99%
“…AHE gene sets mainly target coding regions, whereas UCE gene sets target coding and noncoding genomic regions (Zhang and Lai, 2020c). AHE has been used to uncover phylogenomic relationships of flower flies (Young et al, 2016), lacewings (Winterton et al, 2018;Cai et al, 2023), beetles (Li et al, 2023) and moths (Homziak et al, 2019). UCE has been used for phylogenetic analysis to recover the relationships of many groups, such as fish (Faircloth et al, 2013), arachnids (Starrett et al, 2017), birds (Stiller et al, 2024), wasps (Cooper et al, 2020), and scale insects (Liu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%